Collaboration Between Religion Teacher and Counselor in Shaping Student Morals - Muhammad Chairul Banin; Ummah Karimah; Abdul Basit; Ahmad Irfan; Ahmad Yunus (Program Studi BKPI IAIN Salatiga, 2023)
The purpose of this study was to determine the collaboration between Islamic education teachers and School counselors in shaping student morals. This descriptive qualitative study applied a case study design. Primary data sources were Islamic education teachers, counselors, and students, while secondary data sources were documentation and observation. Data collection techniques using interviews, observation, and document examination. Data validity was confirmed through data triangulation. The results of the research findings show that reward and punishment points through the collaboration of Islamic education teachers and counselors can positively develop students' morals. This study provided all teachers with knowledge and insight regarding the importance of collaboration